Phillygenin Inhibits Helicobacter pylori by Preventing Biofilm Formation and Inducing ATP Leakage - Li, Ru-Jia; Qin, Chun; Huang, Gan-Rong; Liao, Li-Juan; Mo, Xiao-Qiang; Huang, Yan-Qiang (Frontiers in Microbiology, 2022)
With the widespread use and abuse of antibiotics, Helicobacter pylori (H. pylori) has become seriously drug resistant. The development of new antibiotics is an important way to solve H. pylori's drug resistance. Screening antibacterial ingredients from natural products is a convenient way to develop new antibiotics. Phillygenin, an effective antibacterial component, was selected from the natural product, forsythia, in this study. Its minimal inhibitory concentration (MIC) for 18 H. pylori strains was 16–32 μg/ml. The minimum bactericidal concentration (MBC) of H. pylori G27 was 128 μg/ml; the higher the drug concentration and the longer the time, the better the sterilization effect. It was non-toxic to gastric epithelial cell (GES)-1 and BGC823 cells at the concentration of 100 μg/ml. It presented a better antibacterial effect on H. pylori in an acidic environment, and after 24 days of induction on H. pylori with 1/4 MIC of phillygenin, no change was found in the MIC of H. pylori. In the mechanism of action, phillygenin could cause ATP leakage and inhibit the biofilm formation; the latter was associated with the regulation of spoT and Hp1174 genes. In addition, phillygenin could regulate the genes of Nhac, caggamma, MATE, MdoB, flagellinA, and lptB, leading to the weakening of H. pylori's acid resistance and virulence, the diminishing of H. pylori's capacity for drug efflux, H. pylori's DNA methylation, the initiation of human immune response, and the ATP leakage of H. pylori, thus accelerating the death of H. pylori. In conclusion, phillygenin was a main ingredient inhibiting H. pylori in Forsythia suspensa, with a good antibacterial activity, high safety, strong specificity, better antibacterial effect under acidic conditions, and low risk of resistance development by H. pylori. Its mechanism of action was mainly associated with inhibiting the biofilm formation and resulting in ATP leakage. In addition, phillygenin was shown to be able to reduce the acid resistance and virulence of H. pylori.